2004
DOI: 10.1002/ajmg.a.30284
|View full text |Cite
|
Sign up to set email alerts
|

A case of tangier disease with a novel mutation in the c‐terminal region of ATP‐binding cassette transporter A1

Abstract: Tangier disease (TD), a rare disorder characterized by extremely low levels of high density lipoprotein cholesterol (HDL-C), is caused by mutations in the ATP-binding cassette transporter A1 (ABCA1) gene. Here, we describe a new patient with TD. The 42-year-old proband had obvious juvenile cataracts, mild hepatosplenomegaly, and an extremely low level of HDL-C (1 mg/dl), consistent with the diagnosis of TD. The proband was homozygous for a novel CTC6914-6TT --> 2203X mutation in the carboxy terminus of the ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The importance of ABCA1 function as a cholesterol efflux mediator is illustrated by Tangier disease, a genetic disorder characterized by extremely low plasma HDL levels and remarkable accumulation of cholesterol in macrophages localized in the tonsils, spleen, liver, and intestine [Serfaty-Lacrosniere et al, 1994]. Numerous studies have demonstrated that familial Tangier disease mainly results from mutations in the ABCA1 gene [Altilia et al, 2003; Bodzioch et al, 1999; Brooks-Wilson et al, 1999; Guan et al, 2004; Hooper et al, 2009; Maekawa et al, 2009; Rust et al, 1998; Singaraja et al, 2006]. Moreover, macrophages isolated from Tangier patients express significantly lower levels of ABCG1 [Lorkowski et al, 2001].…”
Section: Abcs Are Direct Downstream Targets Of Pparγ1 and Lxrα In Macmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of ABCA1 function as a cholesterol efflux mediator is illustrated by Tangier disease, a genetic disorder characterized by extremely low plasma HDL levels and remarkable accumulation of cholesterol in macrophages localized in the tonsils, spleen, liver, and intestine [Serfaty-Lacrosniere et al, 1994]. Numerous studies have demonstrated that familial Tangier disease mainly results from mutations in the ABCA1 gene [Altilia et al, 2003; Bodzioch et al, 1999; Brooks-Wilson et al, 1999; Guan et al, 2004; Hooper et al, 2009; Maekawa et al, 2009; Rust et al, 1998; Singaraja et al, 2006]. Moreover, macrophages isolated from Tangier patients express significantly lower levels of ABCG1 [Lorkowski et al, 2001].…”
Section: Abcs Are Direct Downstream Targets Of Pparγ1 and Lxrα In Macmentioning
confidence: 99%
“…The importance of ABCA1 function as a cholesterol efflux mediator is illustrated by Tangier disease, a genetic disorder characterized by extremely low plasma HDL levels and remarkable accumulation of cholesterol in macrophages localized in the tonsils, spleen, liver, and intestine [Serfaty-Lacrosniere et al, 1994]. Numerous studies have demonstrated that familial Tangier disease mainly results from mutations in the ABCA1 gene [Altilia et al, 2003;Bodzioch et al, 1999;Brooks-Wilson et al, 1999;Guan et al, 2004;Hooper et Upon uptake of oxLDL by macrophages, oxysterols are synthesized, which allows activation of PPARγ1 and LXRα. Once activated, PPARγ1 and LXRα not only induce the expression of each other, but they also induce the expression of many ABC transporters, as well as that of ApoE.…”
Section: Abcs Are Direct Downstream Targets Of Pparγ1 and Lxrα In Macmentioning
confidence: 99%
“…12 Primary cultures were grown in Dulbecco's modified Eagle's medium (DMEM; Gibco, Grand Island, NY) supplemented with 10% fetal calf serum (FCS; Gibco). The cells were used for the measurements of ASM activity, the cellular lipid efflux, and mRNA expression.…”
Section: Cell Culturementioning
confidence: 99%